Adverse events in patients initiated on dabigatran etexilate therapy in a pharmacist-managed anticoagulation clinic - Donaldson M (Pharmacy Practice, 2013)
Background: Vitamin K antagonists have been the treatment of choice in preventing thromboembolic events, but problems such as frequent dose adjustment and monitoring of coagulation status, including multiple drug and food interactions, make their use difficult. Dabigatran etexilate is a new oral direct thrombin inhibitor not requiring routine monitoring and since its approval in the United States, many clinicians have been interested in utilizing this new therapy. Objective: This study documented adverse drug events (ADEs) recorded in patients started on dabigatran therapy, including those who were previously controlled on warfarin and those who were anticoagulant naïve. Methods: In an outpatient pharmacist-managed anticoagulation clinic, a total of 221 patients were initiated on dabigatran therapy over an 18-month period. 43.0% of these patients were previously controlled on warfarin.Results: 54 of the 221 patients (24.4%) developed an ADE while on dabigatran. The average time to event was 48.4 days. Nine of the fifty-four patients experienced a major bleeding ADE; six patients developed a serious non-bleeding ADE. Five of these fifteen patients died; one death was directly related to dabigatran therapy. The remaining thirty-nine of the fifty-four patients experienced a clinically relevant non-major ADE. Of the fifty-four patients who experienced an ADE, thirty were male. The average age was 73.8 years and the average weight was 92.8kg. Fifty-four percent of those who experienced an ADE were previously anticoagulant naïve.Conclusions: While many clinicians have been interested in utilizing the new direct thrombin inhibitor dabigatran etexilate, this new therapy is not without risks. This study documented adverse drug events in 24.4% of patients who were initiated on dabigatran etexilate therapy over an eighteen month period. ADEs were more common in patients who were anticoagulant naïve prior to dabigatran etexilate therapy and not those who were previously controlled on warfarin therapy.